Pengaruh Gadget dalam Perkembangan Sosial Emosional Anak di TK Pasundan Purwakarta (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is motivated by the use of gadgets in early childhood which has a positive and negative impact. The development of technology and existing information makes everyone inseparable from gadgets. In fact, the use of gadgets given to children must remain under the supervision of parents. Therefore, The objective of this research is to investigate the impact of gadget influencers on the emotional development of children. This study uses qualitative methods. The research results show that gadgets have an influence on children's social emotional development. It can be seen that the influence of gadgets on children's social-emotional development because it includes disruption of children's meental, unstable children's emotions. Therefore, parental monitoring is essential when children utilize electronics.